PMSG in ewes: A Practical and Efficient Step for Superovulation. Issue 1 (April 2021) - Somanjaya, R; Fuah, A M; Rahayu, S; Setiadi, MA; Abdullah, L
Abstract: Ewes have a prolific nature, but in reality, the average number of lambs ( litter size ) is still around 120%. The application of the PMSG ( Pregnant Mare Serum Gonadotrophyn ) hormone aims as a superovulation agent for obtaining twins in one birth. PMSG is a non-pituitary gonadotrophyn hormone that has the same function as FSH (( Follicle Stimulating Hormone ) and LH ( Luteinizing Hormone ) which stimulates follicular and ovulation growth. Various methods of applying the PMSG hormone to the ewes were quite diverse and produced different responses. Which method is considered the most practical and efficient is the main topic in this paper. Details of the discussion in this paper include the nature and biochemical characteristics of PMSG, the performance of PMSG as a superovulation agent, the comparison of PMSG with other reproductive hormones to the superovulation response in ruminants, and the impact of PMSG on superovulation in ewes.